FEATURES OF PNEUMONIA IN HIV-INFECTED PATIENTS - M. T. Vatutin; V. S. Kolesnikov; А. А. Taratorina; Y. V. Yeshchenko; A. V. Filiuk; D. V. Bort (Архивъ внутренней медицины)
The article presents the clinical, diagnostic and treatment features of pneumocystis pneumonia in HIV-infected patients. The clinical case of diagnosis verification in a patient 58 years old with severe respiratory failure is described.